2015
DOI: 10.2174/1874149501509010321
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability Assessment of Reinforced Concrete Framed Structures Considering the Effect of Structural Characteristics

Abstract: Considering the effects of earthquakes occurred during the last 15 years, this article focusses on finding solutions to minimize the human and economic losses. Several methodologies were developed in order to assess the vulnerability of the built environment with special reference to one of the most suitable structural systems in seismic areas for dwellings, offices or other functionalities, which is the reinforced concrete framed structure. Thus, the present article studies the influence on the vulnerability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The seismic vulnerability of the built environment refers to the intrinsic possibility of buildings suffering degradation in the event of a dangerous event of known characteristics-intensity and period of time [40].…”
Section: Seismic Hazardmentioning
confidence: 99%
“…The seismic vulnerability of the built environment refers to the intrinsic possibility of buildings suffering degradation in the event of a dangerous event of known characteristics-intensity and period of time [40].…”
Section: Seismic Hazardmentioning
confidence: 99%
“…Two approaches are stand out in the reliability study: In the first one, the seismic loading is considered as random (Wen and Kwei, 1976;Colangelo et al, 1996;Atkinson and Boore, 2006;Zentner and Borgonovo, 2014;Bouzelha et al, 2017;Arash, 2018;Dorbani et al, 2018;Aliche et al, 2019). In second one, mechanicals and geometrical characteristics of structures are the uncertainties (Hess et al, 2002;Olteanu et al, 2015;Dehmous and Welemane, 2011;Maizia et al, 2017;Xu et al, 2017;Sahu et al, 2019). The second approach is used by varying randomly two variables f c and f y according to their respective distribution laws.…”
Section: Reliability Studymentioning
confidence: 99%
“…A review of the state of assessment of seismic vulnerability caused by natural disasters is the subject of a paper by Vamvatsikos et al [24] Giovinazzi [25] proposed the method for the vulnerability assessment and the damage scenario in seismic risk analysis. Seismic vulnerability assessment, damage scenarios and loss estimation are investigated in the research of Vicente et al [26] Damage assessment of current buildings on a territorial scale is the subject of the research by Giovinazzi and Lagomarsino [27] and Lagomarsino and Giovinazzi [28], and an overview of research activities and present assessments with guidelines for the future were considered in a paper by Atalić et al [29] Fragility and vulnerability analyses of RC-framed buildings, considering the effects of their structural characteristics, were performed by Olteanu et al [30] Medium-and high-rise structures were considered, with four and eight stories, in order to determine the building height in the vulnerability index. Three plan configurations were compared: square, rectangular and L. It was concluded that the structures with fewer levels were more vulnerable than the structures with more levels.…”
Section: Introductionmentioning
confidence: 99%